Protective effects of Pogostemon cablin Bentham water extract on inflammatory cytokine expression in TNBS-induced colitis in rats - Park, Su-Young; Neupane, Ganesh Prasad; Lee, Sung Ok; Lee, Jong Suk; Kim, Mi-Young; Kim, Sun Yeou; Park, Byung Chul; Park, Young-Joon; Kim, Jung-Ae (Archives of pharmacal research, 2014)
In inflammatory bowel disease (IBD), colon epithelial cells express a variety of inflammatory mediators, including chemokines, which perpetuate inflammatory response. In the current study, we report that water extract of Pogostemon cablin Bentham aerial parts (PCW), which has traditionally been used for treatment of the common cold and infectious disease, suppressed colon inflammation. Treatment with PCW resulted in effective inhibition of tumor necrosis factor (TNF)-α-induced adhesion of monocytes to HT-29 human colonic epithelial cells. In a trinitrobenzene sulfonic acid (TNBS)-induced rat model of IBD, PCW suppressed clinical signs of colitis, including weight loss, colon tissue myeloperoxidase activity, a marker for inflammatory cell infiltration, and cyclooxygenase-2 expression in a dose-dependent manner. In addition, PCW suppressed TNBS-induced mRNA expression of IL-8, MCP-1, and IL-6 in rat colon. The nuclear level of NF-κB in TNBS-treated rat colon and NF-κB luciferase reporter gene activity in TNF-α-treated HT-29 cells were significantly inhibited by PCW. Taken together, the results of this study suggest that PCW suppressed colon inflammation via suppression of NF-κB-dependent expression of pro-inflammatory cytokines.